PERAN KOMISARIS INDEPENDEN DALAM MEMODERASI HUBUNGAN FINANICIAL DISTRESS DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Bayhaki, Muhamad Rizki; Suciati Mu’anifah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research seeks to identify the function of independent commissioners in influencing the connection between financial distress and audit tenure on the reliability of financial statements in firms involved in the infrastructure sector listed on the Indonesia Stock Exchange from 2019 to 2023. The subject of this research consists of infrastructure sector firms registered on the Indonesia Stock Exchange, totaling 67 companies as of 2023. This study employs a purposive sampling method, selecting 9 companies over a 5-year observation period, resulting in a total sample of 45 data points. The employed analysis technique is a descriptive statistical approach utilizing a moderation regression analysis tool. Hypothesis testing is conducted utilizing Eviews 12 software. The findings of this research suggest that (1) Financial Distress and Audit Tenure concurrently impact the integrity of financial statements, (2) Financial Distress negatively influences the integrity of financial statements, (3) Audit Tenure does not affect the integrity of financial statements, (4) Independent Commissioners do not moderate the connection between financial distress and the integrity of financial statements, (5) Independent Commissioners do not moderate the relationship between audit tenure and the integrity of financial statements.